Improvement of Traffic in Some Streets in Baghdad City Using GIS Pictures - Kadhim, Amany (Iraqi Journal of Science, 2025)
Traffic collisions may happen in any location of the street for many reasons, careless drivers, narrow roads, badly designed intersections and traffic signals, are some of the reasons. When the collisions are repeated in a specific location, the case must be studied and solutions must be found to eliminate these collisions.A GIS is a kind of super map, computer software that links geographic information (where things are) with descriptive information (what things are like). Unlike a flat paper map, where what you see is what you get, a GIS can have many layers of information underneath its surface.In this paper GIS is used as a tool to examine, analyze, and suggest solutions for areas where traffic collisions have occurred in three selected streets in the city of Baghdad. Al-Kifah Street, Sheikh Omar Street, 14 Ramadan Street (Arbataash Ramadan St.), was chosen for this research. These streets are very busy and old.Data types that are employed are; firstly and more important accidents by location, cause, date, time of day, type of vehicle, and severity (property damage only, injuries, or fatality).It was found that most of the collisions are broadsides and the conclusion is that the traffic signals along these streets aren't giving people enough time to clear the intersection. The suggestion is mainly to keep the yellow light on longer so traffic can clear.